The Most Frequent Types of Tasks in Czech Biology Textbooks - Vránová, Olga (e-Pedagogium, 2008)
This article is concerned with tasks evaluation in biology textbooks. Twenty five textbooks of the Fortuna, Fraus, Jinan, Prodos, Scientia and SPN publishing houses were analysed. This study was concentrated on the number, difficulty and diversity of tasks in each textbook. The difficulty of tasks was classified according to Tollingerová. Tasks of simple cognitive level were the most frequent ones.
Keywords: Biology textbooks; learning tasks; types of tasks; task evaluation